High life, low life - Battersby, Alan (Cambridge English readers. Level 4, 2001)
Grand Central Station, New York in mid-July. It's early morning, but everyone is suffering in the heat. Private investigator Nathan Marley is on his way to another wasted day at the office. But a chance meeting with a homeless woman at the station and a surprise letter changes all of that. Marley starts a journey through parts of the burning summer city he has never visited.